The Effect Of Institutional Ownership, Capital Structure And Liquidity On Earnings Quality In The Primary Consumer Goods Sector Listed On The Idx In 2014-2024 - Valentin, Michel; Hotang, Keri Boru; Widianingsih, Indi (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2025)
Purpose – This study aims to obtain empirical evidence on the Influence of Institutional Ownership, Capital Structure and Liquidity on Eranings Quality Design/methodology/approach – This study uses quantitative research. The sample in this study is companies in the primary consumer goods sector listed on the Indonesia Stock Exchange during 2014-2024 as many as 24 companies selected through purposive sampling. The analysis technique used was multiple linear regression with the help of the E-views 9 software . Findings – The results of this study found that Institutional Ownership has an effect but statistically does not have a significant effect on Earnings Quality, Capital Structure is influential but statistically significant affects Earnings Quality and Liquidity has no effect but statistically significant affects Earnings Quality. Research limitations/implications – This study discusses Institutional Ownership, Capital Structure and Liquidity on Earnings Qualitywith the primary consumer goods sector listed on the Indonesia Stock Exchange.